The effect of bacon pump retention levels following thermal processing on bacon slice composition and sensory characteristics. (June 2018) - Sivendiran, T.; Wang, L.M.; Huang, S.; Bohrer, B.M.
Abstract: The objective was to evaluate the effect of belly pump uptake and cook yield during processing on bacon slice composition and sensory attributes. A total of forty-four bellies were commercially sourced and randomly assigned to two experiments. Each experiment consisted of one smokehouse cooking cycle. Within each experiment, bellies were separated at the medial point and one belly half was assigned to a high pump uptake treatment (HIGH; target of 30% uptake) and the remaining belly half was assigned to a normal pump uptake treatment (NORM; target of 15% uptake). In experiment-1, cook yields were 107.79% for the HIGH bellies and 101.52% for the NORM bellies. In experiment-2, cook yields were 97.41% for the HIGH bellies and 94.74% for the NORM bellies. Overall, bacon slice composition and sensory attributes of bacon from bellies with greater pump retention were largely unaffected, accordingly it was concluded that cook yields ranging in level of pump retention does not affect most attributes of bacon.